ETIKA DALAM PROGRAM HIBURAN TELEVISI - Azwar, Azwar; Pradyanti, Alifia; Hidayah, Nisfa Siti Elfianti (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2018)
Entertainment programs in the television are currently being criticized by the public. Not only criticism, even some entertainment programs on television received reprimands from the Indonesian Broadcasting Commission (Komisi Penyiaran Indonesia-KPI). This is due to many entertainment programs that use jokes that exceed the limits of reasonableness. Therefore, this study aims to describe how ethics in entertainment programs on television stations, as well as the effects that can be caused to the public on quality and ethical entertainment programs. In this case, research on the NET TV station was emphasized in the Waktu Indonesia Bercanda program. This research is important, considering that many entertainment programs are consumed by the public through television media. On NET TV itself, the entertainment program presented reaches 50% of all existing program. Waktu Indonesia Bercanda is a TV program that is categorized as an entertainment program in the form of a quiz show and dexterity in thinking. Waktu Indonesia Bercanda also performed the program casually and inserted with their typical jokes, but still ethical. Ethics here is not to criticize, to hurt the hearts and physicalities of others and things that have other negative meanings.